1982
DOI: 10.1111/j.1748-1716.1982.tb07152.x
|View full text |Cite
|
Sign up to set email alerts
|

Store and recoil of elastic energy in slow and fast types of human skeletal muscles

Abstract: Stretch-shortening cycle refers to the mechanical condition in which store and recoil of elastic energy occur in the skeletal muscle. This leads to a greater work output when compared to a simple shortening contraction. The subjects performed vertical jumps with and without preliminary counter-movement and with small and large knee angular displacement. The results indicated that those subjects who had more fast twitch (FT) fibers benefited more from the stretching phase performed with high speed and short ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
3
13

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(89 citation statements)
references
References 10 publications
1
72
3
13
Order By: Relevance
“…We found that slow fibres (control soleus) exhibited a compliance value lower than that of fast fibres (control EDL). In the whole muscle, using fibre typing by ATPase staining, other authors have shown that type I and type I1 fibres may have different elastic properties (Bosco et al 1982). These authors observed that, in human subjects performing vertical jumps, fast-type fibres in the vastus lateralis muscle stored more elastic energy than slow-type fibres.…”
Section: Elastic Characteristicsmentioning
confidence: 53%
See 1 more Smart Citation
“…We found that slow fibres (control soleus) exhibited a compliance value lower than that of fast fibres (control EDL). In the whole muscle, using fibre typing by ATPase staining, other authors have shown that type I and type I1 fibres may have different elastic properties (Bosco et al 1982). These authors observed that, in human subjects performing vertical jumps, fast-type fibres in the vastus lateralis muscle stored more elastic energy than slow-type fibres.…”
Section: Elastic Characteristicsmentioning
confidence: 53%
“…Differences in the elastic behaviour of fast and slow muscles have been suggested from studies on whole muscles (Bosco et al 1982;Goubel & Marini, 1987;Pousson et al 1991). However, only a few studies (McDonald & Fitts, 1995;Galler et al 1996) have reported data on the elastic characteristics of single muscle fibres.…”
Section: Introductionmentioning
confidence: 99%
“…26 Behm and Chaouachi 1 indicated that increased muscle compliance (less muscle stiffness) can enhance the ability of the musculotendinous unit to store elastic energy over a longer period. [27][28][29] Although the increased compliance associated with static stretching is implicated in the impairment of rapid SSC actions, such as sprinting and hurdle jumps, more prolonged SSC actions can benefit from a more compliant musculotendinous unit. 1 For example, Wilson et al 30 reported a 5% increase in rebound bench press after 8 weeks of flexibility training.…”
Section: Discussionmentioning
confidence: 99%
“…74 While the energy that is absorbed during the muscle and tendon stretch is often dissipated as heat, elastic strain energy can also be stored and recovered if an immediate shortening concentric contraction follows. 4,12,25,51,59 When muscles are activated eccentrically immediately prior to shortening, they no longer act as shock absorbers; rather, they perform more like springs 115,116 ( Figure 1). …”
Section: Eccentric Contractions: Muscles Operating As Shocks or Springsmentioning
confidence: 99%